Active Rectifier for Uninterruptable Power Supply - Stepanov, Andrew; Bogdans, Valdis; Suskis, Pavel; Galkin, Ilya (Electrical, Control and Communication Engineering, 2010)
The paper contains analysis of power factor correction circuits that is made in the context of elaboration of uninterruptable power supply system. Various correctors have been estimated analytically, by means of simulation and experimentally. The most significant attention has been paid to the efficiency of the analyzed converters and their compatibility with modular approach to development of power converters.